BAPETEN SUPERVISORY AUTHORITY IN THE PROCEDURE OF TRANSPORTATION OF RADIOACTIVE SUBSTANCE THROUGH THE SEA - Shinta Hadiyantina; Dewi Cahyandari; Dhiana Puspitawati (Faculty of Law, Universitas Sebelas Maret, 2019)
One important thing that must be considered in the use of nuclear and other radioactive materials is the process of transporting radioactive substances through the sea. This paper will analyze the optimization of the supervisory authority of BAPETEN in the transportation of radioactive substances, especially in the process of transporting radioactive substances by sea. Option to choose the sea because most of Indonesia's territory is the sea. If it has the authority, Bapeten's supervisory authority will then be analyzed in the process of transporting radioactive substances via the sea lane. Recommendations from this article are a form of juridical liability if an error occurs, which causes a loss in the process of transporting radioactive substances by sea. Because the process of transporting radioactive substances is essential in preventing the occurrence of radiation, the regulatory authority in the transportation process must be regulated in detail based on the precautionary principle, as well as the form of juridical accountability.